How do MNEs invent? An invention-based perspective of MNE profitability - Kafouros, Mario; Hashai, Niron; Tardios, Janja Annabel; Wang, Elizabeth Yi (Journal of International Business Studies, 2022)
Abstract Although MNEs create inventions both internally and collaboratively with partners as well as within and across countries, we know very little about the effects that combining such inventive activities have on their profitability. This study develops an invention-based perspective that considers how MNEs' profitability is influenced by the ways they organize the development of inventions across organizational boundaries (internally or collaboratively) and geographic boundaries (within or across countries). This perspective postulates that profitability is not merely driven by advantageous technological endowments but also by how such technological assets have been created. Accordingly, it explains why specific combinations of inventive activities across the two boundaries affect the likelihood of creating breakthrough inventions differently, provide different revenue and cost advantages, and have different effects on MNEs’ profitability. It further explains why cross-country inventions contribute more to profitability when they are internalized, while within-country inventions are more profitable when they are created collaboratively.